BA 291 - Business Process Management - Linn Benton Virtual College (2018)
The course helps you identify information-bearing events, assess and improve process efficiency, learn to model and analyze business processes, recognize probabilistic components of business processes, and understand the interactions between human behavior and process design. Hands-on, case-based course work allows you to practice some of the principles addressed. You will demonstrate the ability to utilize business computer applications. Course Outcomes: